2010
DOI: 10.1021/jo101910r
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of (+)-Epilupinine via An Intramolecular Nitrile Oxide-Alkene Cycloaddition

Abstract: Total synthesis of (+)-epilupinine was accomplished in nine steps and in 48% overall yield, in which INOC was used as the key step for the construction of the quinolizidine skeleton. We found that it was an extremely difficult task to prepare the key intermediates (R)-N-(3-nitropropyl)-2-vinylpiperidine or (R)-(2-vinylpiperid-1-yl)propanal by routine methods. Thus, by using Fukuyama's oxime synthesis, a general method was developed for highly efficient conversion of 3-(N,N-dialkylamino)propanols into 3-(N,N-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…We then focused on advancing the cycloadduct toward the synthesis of lepadin F. The deoxygenation of ketone 8 wasa ttempted to obtain methylene product 13 first. Unfortunately, the classical methods, such as Caglioti-Wolff-Kishner reduction, [20] thioacetal-based reduction, [21] Yamamura-Clemmensen reduction, [22] and its Arimoto variant, [23] all were unsuccessful. Thus, triol 9 was employedt oa chieve the subsequents ynthesis (Scheme 3).…”
Section: Resultsmentioning
confidence: 99%
“…We then focused on advancing the cycloadduct toward the synthesis of lepadin F. The deoxygenation of ketone 8 wasa ttempted to obtain methylene product 13 first. Unfortunately, the classical methods, such as Caglioti-Wolff-Kishner reduction, [20] thioacetal-based reduction, [21] Yamamura-Clemmensen reduction, [22] and its Arimoto variant, [23] all were unsuccessful. Thus, triol 9 was employedt oa chieve the subsequents ynthesis (Scheme 3).…”
Section: Resultsmentioning
confidence: 99%
“…(+)-Epilupinine has been shown to exhibit in vitro inhibitory activity against Leukaemia P-388 (LD50 = 28 μg/mL) and lymphocytic Leukaemia L1210 (LD50 = 28 μg/mL) cells . Both natural products have been the focus of considerable synthetic attention and have been prepared by total synthesis in racemic and enantiomerically enriched form. …”
mentioning
confidence: 99%
“…An instructive example of what might happen in the absence of protonic catalysis emerges from the work of Wang, Hu, and collaborators, who found that the treatment of oxime 50 with DIB in methanol / catalytic TFA failed to produce the desired 51 (Scheme 14; decomposition of 50). 22 It is likely that the basic amine neutralized the TFA, thereby denying protonic catalysis to the process and opening the door to side reactions. A limitation of the above methodology is that the formation of isoxazoles from terminal alkynes is inefficient.…”
Section: Scheme 12 Approach To Cortistatin Via Tandem Phenolic Alkoxmentioning
confidence: 99%